Synergistic interaction between the type III secretion system of the endophytic bacterium Pantoea agglomerans DAPP‐PG 734 and the virulence of the causal agent of olive knot Pseudomonas savastanoi pv. savastanoi DAPP‐PG 722. (16th July 2021) - Moretti, Chiaraluce; Rezzonico, Fabio; Orfei, Benedetta; Cortese, Chiara; Moreno‐Pérez, Alba; van den Burg, Harrold A.; Onofri, Andrea; Firrao, Giuseppe; Ramos, Cayo; Smits, Theo H. M.; Buonaurio, Roberto
Abstract: The endophytic bacterium Pantoea agglomerans DAPP‐PG 734 was previously isolated from olive knots caused by infection with Pseudomonas savastanoi pv. savastanoi DAPP‐PG 722. Whole‐genome analysis of this P. agglomerans strain revealed the presence of a Hypersensitive response and pathogenicity ( Hrp ) type III secretion system (T3SS). To assess the role of the P. agglomerans T3SS in the interaction with P . savastanoi pv. savastanoi, we generated independent knockout mutants in three Hrp genes of the P. agglomerans DAPP‐PG 734 T3SS ( hrpJ, hrpN, and hrpY ). In contrast to the wildtype control, all three mutants failed to cause a hypersensitive response when infiltrated in tobacco leaves, suggesting that P. agglomerans T3SS is functional and injects effector proteins in plant cells. In contrast to P . savastanoi pv. savastanoi DAPP‐PG 722, the wildtype strain P . agglomerans DAPP‐PG 734 and its Hrp T3SS mutants did not cause olive knot disease in 1‐year‐old olive plants. Coinoculation of P . savastanoi pv. savastanoi with P. agglomerans wildtype strains did not significantly change the knot size, while the DAPP‐PG 734 hrpY mutant induced a significant decrease in knot size, which could be complemented by providing hrpY on a plasmid. By epifluorescence microscopy and confocal laser scanning microscopy, we found that the localization patterns in knots were nonoverlapping for P . savastanoi pv. savastanoi and P. agglomerans when coinoculated. Our results suggest that suppression of olive plant defences mediated by the Hrp T3SS of P. agglomerans DAPP‐PG 734 positively impacts the virulence of P . savastanoi pv. savastanoi DAPP‐PG 722. Abstract : The presence of an active Hrp ‐1 T3SS in Pantoea agglomerans (Pag) DAPP‐PG 734 can suppress plant defences and therefore Pag synergistically interacts with Pseudomonas savastanoi pv. savastanoi DAPP‐PG 722 inside the olive knot.